Time to choose climate change for good - Isaac, Oscar 1979- (Ro*Co Films Educational, 2016)
Climate change is the biggest challenge humanity has ever faced - and it is also our greatest opportunity. We have the solutions we need, but we are in a race against the clock to implement them in time. Oscar-winning documentary director Charles Ferguson captures the urgency and innovation of this critical moment in his new film, TIME TO CHOOSE which takes audiences on a journey from the threats we face to the remarkable stories of people changing our world for the better. TIME TO CHOOSE also delivers a clear message to audiences: we can take action to stop this global threat. It is the first major film to offer compelling stories of the innovators, leaders and average people fighting on the front lines for a cleaner, more sustainable world-Movie website. Ferguson explores the comprehensive scope of the climate change crisis and examines the power of solutions already available. Through interviews with world-renowned entrepreneurs, innovators, thought leaders and brave individuals living on the front lines of climate change, Ferguson takes an In-depth look at the remarkable people working to save our planet
Keywords: Climatic changes; Feature films; Nonfiction films; Documentary films; Film; DVD-Video